Meningkatkan Pemahaman IPA dengan Model Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas V SDN Kertobanyon - Septyana Dwi Kusuma Wardani; Nurul Kusuma Dewi; Tri Susi Artina Wati (Politeknik Kampar, 2024)
The purpose of this study was to determine the extent to which fifth grade students of SDN Kertobanyon were able to master the science subject